Отбор чувствительных к бактериофагу λ клонов из устойчивого к нему штамма Escherichia coli - Славченко, И.Ю. (Біополімери і клітина, 2001)
A method of selection of the phage λ sensitive clones from the population of the bacteriophage λ resistant cells using the phage λcI857ApRTcR has been theoretically formulated and experimentally approved. The isolation was realized as follows. The phage λ resistant E. coli strain was infected by phage λ, which introduces antibiotic-resistance markers into the cell. The sensitive to phage λ vir and lysing at 43 °C clones were isolated on the selective medium. The frequency of occurrence of such cells in the population was 10⁻⁶ . The presence of ts-mutation in the phage cI gene has allowed to cure the cells from phage λcI857ApRTcR during cultivation of these cells under non-selective conditions at increased temperature and to obtain the phage A sensitive clones originated from resistant E. coli strain. The method can also be used for the estimation of the E. coli populations heterogeneity by a given feature.